A feed-forward regulatory loop between androgen receptor and PlncRNA-1 promotes prostate cancer progression. Issue 1 (28th April 2016) - Fang, Ziyu; Xu, Chen; Li, Yaoming; Cai, Xiaobing; Ren, Shancheng; Liu, Houqi; Wang, Yue; Wang, Fubo; Chen, Rui; Qu, Min; Wang, Yang; Zhu, Yasheng; et al.
Highlights: PlncRNA-1 is an lncRNA whose transcription is promoted by AR and that primarily localizes to the cytoplasm. PlncRNA-1 promotes PCa growth via a mechanism dependent on microRNAs. PlncRNA-1 and its regulating AR transcripts are both targeted by miR-34c and miR-297. The expression of PlncRNA-1 and AR is inversely correlated with the expression of miR-34c and miR-297 in PCa tissue samples. Abstract: We previously reported that PlncRNA-1, a long non-coding RNA that is up-regulated in prostate cancer (PCa), affects the proliferation and apoptosis of PCa cells. However, the molecular mechanisms underlying these effects remain largely unknown. In this study, we demonstrated that long non-coding RNA PlncRNA-1, whose expression is promoted by Androgen Receptor (AR), protects AR from microRNA-mediated suppression in PCa cells. PlncRNA-1 knockdown resulted in the up-regulation of a series of AR-targeting microRNAs, among which miR-34c and miR-297 were found to regulate both AR and PlncRNA-1 expression at the post-transcriptional level. Functional analysis revealed that miR-34c and miR-297 overexpression down-regulated AR expression and inhibited the expression of downstream AR targets and that PlncRNA-1 overexpression rescued these effects. The association of PlncRNA-1 with tumor progression was also evaluated in mouse xenograft models, PCa tissues (16 paired samples), and blood samples (35 biopsy-negative and 37 biopsy-positive). Together, the data generated in this study indicate that PlncRNA-1 sponges AR-targeting microRNAs to protect AR from microRNA-mediated down-regulation and that these events form a regulatory feed-forward loop in the development of PCa. These findings suggest that PlncRNA-1 might potentially serve as a novel biomarker in PCa and that PlncRNA-1 might warrant further investigation to determine its potential role as a promising therapeutic target in PCa.